2019
DOI: 10.1016/j.pharmthera.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in major depressive disorder: From pathophysiology to therapy

Abstract: In spite of promising preclinical results there is a decreasing number of new registered medications in major depression. The main reason behind this fact is the lack of confirmation in clinical studies for the assumed, and in animals confirmed, therapeutic results. This suggests low predictive value of animal studies for central nervous system disorders. One solution for identifying new possible targets is the application of genetics and genomics, which may pinpoint new targets based on the effect of genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 272 publications
2
48
0
4
Order By: Relevance
“…Findings of subtypes with distinct profiles of brain abnormalities may reveal the potential neurobiological substrates of key sources of heterogeneity in depression ( Price et al, 2017a , Williams, 2016 ). Additionally, inflammation and oxidative stress could also be implicated in differentiating the distinct subtypes of depression ( Gonda et al, 2019 ). Moreover, subgroups of individuals with MDD characterized by differing brain abnormalities may reflect qualitatively distinct genetic factors influence in the illness trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of subtypes with distinct profiles of brain abnormalities may reveal the potential neurobiological substrates of key sources of heterogeneity in depression ( Price et al, 2017a , Williams, 2016 ). Additionally, inflammation and oxidative stress could also be implicated in differentiating the distinct subtypes of depression ( Gonda et al, 2019 ). Moreover, subgroups of individuals with MDD characterized by differing brain abnormalities may reflect qualitatively distinct genetic factors influence in the illness trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Our results add to the long debate and ever-expanding research focusing on the relative role of nature or nurture, that is, biological or environmental contributors in the development and severity of depression ( 26 ). Although genetic approaches including both candidate gene and GWAS studies generally fail to provide replicable and conclusive results ( 14 , 27 ), temperaments, which develop on a strong genetic and biological basis ( 28 ), influence neuroendocrine and autonomic processes ( 29 ) and determine emotional and behavioral reactivity with an early manifestation and strong temporal stability, have been repeatedly shown to be associated with depression ( 30 32 ). While most temperamental models were developed on theoretical bases to describe the biological core of the healthy personality, specifically the model of affective temperaments was derived, besides drawing form theoretical underpinnings from Hippocrates, Kraepelin, and Kretschmer, from the observation of affective disorder patients and their healthy first-degree relatives ( 10 , 24 ), The pathoplastic role of affective temperaments in affective disorders were subsequently confirmed by a large number of independent studies ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a continuum in case of different manifestations of depression depending on the relative contribution of environmental and genetic determinants from more “reactive” to more “endogenous” forms, however, although with differing weight, both biological/genetic and environmental contributors are necessary for the emergence of depression which develops in the interaction of these two major factors ( 12 – 14 ). That is, environmental events trigger depression in those who carry a biological/genetic predisposition such as in the form of innate affective temperaments, or this biological/genetic predisposition increases sensitivity towards environmental events and leads to the manifestation of depression only in case of exposure to stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacogenetic studies have indicated that genomic variations are one of the critical biological factors that prominently affect the individual differences of antidepressant response, in which common single nucleotide polymorphisms (SNPs) are estimated to explain 50% or more of the variation of the antidepressant response 9 . Nevertheless, previous findings from candidate gene approaches have been poorly replicated, with insufficient predictive power to be useful in clinical practice and analytical problems of uncontrolling population stratification or genetic heterogeneity 10,11 . In addition, so far a total of eight genome-wide association studies (GWAS) of antidepressant effectiveness have been carried out mainly in Caucasian ancestry populations (eight clinical studies, ten published articles); none of these studies have found a genetic variant that achieved genome-wide significance [12][13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%